Cilia‐localized LKB1 regulates chemokine signaling, macrophage recruitment, and tissue homeostasis in the kidney. (19th June 2018) - Viau, Amandine; Bienaimé, Frank; Lukas, Kamile; Todkar, Abhijeet P; Knoll, Manuel; Yakulov, Toma A; Hofherr, Alexis; Kretz, Oliver; Helmstädter, Martin; Reichardt, Wilfried; Braeg, Simone; Aschman, Tom; et al.
Abstract: Polycystic kidney disease (PKD) and other renal ciliopathies are characterized by cysts, inflammation, and fibrosis. Cilia function as signaling centers, but a molecular link to inflammation in the kidney has not been established. Here, we show that cilia in renal epithelia activate chemokine signaling to recruit inflammatory cells. We identify a complex of the ciliary kinase LKB1 and several ciliopathy‐related proteins including NPHP1 and PKD1. At homeostasis, this ciliary module suppresses expression of the chemokine CCL2 in tubular epithelial cells. Deletion of LKB1 or PKD1 in mouse renal tubules elevates CCL2 expression in a cell‐autonomous manner and results in peritubular accumulation of CCR2 + mononuclear phagocytes, promoting a ciliopathy phenotype. Our findings establish an epithelial organelle, the cilium, as a gatekeeper of tissue immune cell numbers. This represents an unexpected disease mechanism for renal ciliopathies and establishes a new model for how epithelial cells regulate immune cells to affect tissue homeostasis. Synopsis: The cilium instructs immune cell behaviour and tissue homeostasis via a complex of ciliopathy‐related proteins and the kinase LKB1 that together regulate chemokine signalling. Dysregulation of this system presents an unexpected disease mechanism for ciliopathies. The primary cilium transmits a signal that activates expression of chemokine CCL2. This signal is regulated through an intra‐ciliary complex of LKB1, NPHP1, polycystin 1 (PC1), ANKS3 and NEK7. Loss of LKB1 or PC1 increases CCL2 expression and peritubular macrophage numbers and promotes ciliopathy phenotypes. The Polycystic Kidney Disase (PKD) phenotype seen upon PKD1 depletion is ameliorated in the absence of cilia or tubular CCL2. Abstract : A kidney‐specific inactivation of metabolic sensor LKB1 complex reveals a functional crosstalk between primary cilia signaling and aberrant immune cell activation in vivo .